Executive turnover in China's state-owned enterprises: Government-oriented or market-oriented? - Feng Liu; Linlin Zhang (China Journal of Accounting Research, 2018)
Executive turnover is important in the governance of state-owned enterprises (SOEs). Herein, we focus on the executive turnover of China's SOEs, and the implementation of related evaluation mechanisms under different levels of government intervention. We collect executive turnover data of listed Chinese SOEs from 1999 to 2012, and find that about half of the SOE executives leave office within two terms, which is in line with government recommendations. Moreover, we find that more than a third of executives leave after less than one term, and nearly 20% after more than two terms, highlighting the uncertainty and unpredictability of executive appointments in SOEs. We also find that the executive evaluation mechanism for SOEs is implemented differently under different levels of government intervention. SOEs under weak intervention, such as those controlled indirectly by governments, controlled with low shareholdings, from non-regulated industries or in the Eastern regions, prefer the market-oriented evaluation method, which places more weight on executives' economic performance. In contrast, those under strong intervention prefer the government-oriented evaluation method, which is characterized by policy burden.
Keywords: 650; Executive turnover; China's state-owned enterprises; Performance; Policy burden; Managerial market